2005
DOI: 10.1292/jvms.67.787
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 Contributes to Phorbol Ester-Induced Ca2+-Independent Contraction of Pulmonary Artery Smooth Muscle

Abstract: ABSTRACT. We determined the contribution of the Rho family of low molecular GTP-binding proteins to phorbol ester-induced contraction in swine pulmonary artery smooth muscle. In Ca 2+ -free medium containing 1 mM EGTA, 12-deoxyphorbol 13-isobutyrate (DPB, 1 µM), a protein kinase C (PKC) activator, elicited sustained contractions, which were not inhibited by treatment with verapamil, a voltagedependent Ca 2+ channel antagonist, and Y27632, a Rho-associated kinase inhibitor. Immunoblot analysis showed three PKC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Possible targets for DAG include the PKC family of protein kinases, consistent with previous studies that placed MLK3 downstream of PKC [18]. Interestingly, it has been shown that phorbol ester-treatment leads to PKC-dependent activation of Cdc42 and Rac1 [8]. This mechanism could contribute to the activation of Cdc42 and Rac1 by SFA.…”
Section: Discussionsupporting
confidence: 77%
“…Possible targets for DAG include the PKC family of protein kinases, consistent with previous studies that placed MLK3 downstream of PKC [18]. Interestingly, it has been shown that phorbol ester-treatment leads to PKC-dependent activation of Cdc42 and Rac1 [8]. This mechanism could contribute to the activation of Cdc42 and Rac1 by SFA.…”
Section: Discussionsupporting
confidence: 77%
“…Major functions of ARF6 include cytoskeletal organization and actin remodeling, roles in endocytosis and vesicular trafficking, cell adhesion, and completion of mitotic cytokinesis in different cell types (D'Souza-Schorey and Chavrier, 2006;Donaldson, 2002;Hongu and Kanaho, 2014;Humphreys et al, 2013;Klein et al, 2006;Luton, 2005;Schafer et al, 2000;Schweitzer and D'Souza-Schorey, 2005). Accordingly, it promotes processes based on actin assembly and cytoskeletal organization, including migration, branching and outgrowth in neuronal cells, filopodia extension, platelet-mediated clot formation and thrombosis, or tumor angiogenesis and metastasis (Charles et al, 2016;Choi et al, 2005;Gauthier-Campbell et al, 2004;Hiroi et al, 2006;Hongu et al, 2016;Miura et al, 2016;Torii et al, 2010;Urban et al, 2016). With NAV2729, a small molecule inhibitor with presumed specificity for ARF6 is available (Yamauchi et al, 2017;Yoo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, however, this was the only study directly reporting the role of CDC42 in smooth muscle contraction, that is, by showing smooth muscle contraction of intact tissues. Although other studies repeatedly suggested a similar role and suggested involved mechanisms, this evidence stayed preliminary and included demonstration of Cdc42 activation by contractile agonists and Cdc42 induced actin organization in smooth muscle cells (Choi et al, 2005; Fediuk, Sikarwar, Nolette, & Dakshinamurti, 2014; Q. F. Li & Tang, 2009; Tang & Gunst, 2004; Tang, Zhang, & Gunst, 2005; Zhang, Huang, & Gunst, 2016). Consequently, it has been assumed that Cdc42 promotes smooth muscle contraction by actin polymerization and filament organization but not via MLC phosphorylation (Figure 1), what involves most probably Wiskott–Aldrich Syndrome protein family members (Puetz et al, 2009).…”
Section: Cdc42 In Smooth Muscle Contractionmentioning
confidence: 89%